Research on Activation Design of Street Leftover Spaces on the Main Island of Macao Based on Industry 4.0 and Propagation Models. (4th March 2022) - Shi, Ruiting; Wang, Xiaoxiao; Huang, Chen; Liang, Siyang
Abstract : Space has become a driver not only for knowledge, inspiration, cooperation, and policymaking, but also for high-end technology integration into the manufacturing domain. As the high-density city quarters, the Macau Peninsula carries multiple functions via its public outdoor spaces, and they are of vital significance. Closely intertwined with Industry 4.0 is therefore the next industrial revolution that is already showcasing the benefits of increased connectivity, intelligence, and flexible automation. The rapid urbanization of Macao was not guided by sound land use planning, induced the scattering of many negative spaces on narrow streets. Because of their irregular shapes and utilization difficulties, these spaces gradually become leftover spaces. A number of measurement-based street leftover spaces models have been developed over the years by researchers as well as standards bodies to model path in typical wireless environments. In this paper, the streets of Macao are analyzed based on the city characteristics. The pedestrians and spatial relationships are investigated via space syntax and SPSS regression fitting. Finally, activation design of street leftover spaces is conducted, for making better use of leftover spaces, compensate for the functional deficiencies of streets, and endow them with more vigor and vitality.